Diseño de un entorno virtual interactivo para la formulación de conjeturas en el tema de sucesiones - Herrera Alva, Juan Gabriel (2025)
This study focuses on the design of the first phase of an interactive virtual work environment (IVE) that aims to facilitate the development and formulation of conjectures on the topic of real number sequences. A hypothetical learning trajectory (HLT) was designed as a didactic framework for the IVE. The HLT is intended to support planned and active learning in science students. It includes six examples of sequences for learning the concepts of monotonic sequences, bounded sequences, and convergent sequences, and guides reflection for developing conjectures. The IVE has fourteen tasks designed based on the theoretical constructs of the image and the definition of a concept. The decisions for the design of the IVE are documented, and the results of a pilot test are presented, highlighting the development of at least one conjecture in four of the seven participants.